Rare case of intraintestinal stromal tumors in the patient with familial adenomatous polyposis - Lozynska, M.R.; Pospishil, Y.O.; Varyvoda, O.Y.; Plawski, A.; Pretsel, O.O. (Experimental Oncology, 2015)
Aim: To describe the case of metachronous gastrointestinal stromal tumors in a proband with familial adenomatous polyposis (FAP), carrier of APC gene mutation in codon 1309. Material and Methods: The physical examination, genealogical analysis and molecular genetic analysis of peripheral blood in 15-years-old girl with FAP and her sister, were carried out. Macroscopic, standard histological and immunohistochemical study of surgical specimens — intraintestinal tumors of the small intestine in proband was performed. Results: Extraintestinal manifestations, including congenital abnormalities of facial skeleton, typical for Gardner’s syndrome, were observed in the sisters with FAP as the addition symptoms of the disease. Frameshift mutation in codon 1309 in the APC gene was detected in these patients. A rare neoplasia — metachronous gastrointestinal stromal tumor was found in proband 15 months after total colectomy for FAP. This is the third case described in the accessible medical literature. Conclusion: The possible role of APC gene mutation in the development of mesenchymal neoplasms is discussed. The study of stromal tumors is important for understanding of their pathogenesis that will enable to develop effective targeted therapy. Key Words: familial adenomatous polyposis, extraintestinal manifestations, APC gene mutations, gastrointestinal stromal tumors.